(untitled) (Comprehensive Journal of Science, 2025)
This study examines an application that contributes to international efforts in providing financial reporting standards (IFRS). It identifies the greatest interaction with financial reports and the extent of international application required for the quality of financial reports. Despite the growing trend toward international decision-making, there is a discrepancy in the extent of shareholders’ commitment to them, and they compete to contribute to the quality of financial reporting. Hence, the research problem is: - What is an application similar to the International Financial Reporting Standards (IFRS) on the quality, accuracy, and transparency of financial reports by companies? The aim of this study is to identify the nature of IFRS data, analyze the extent to which the application of this information impacts the quality of financial reports, examine the challenges facing international application in local environments, and provide better ideas for designing IFRS data in organizations. - The research relied on descriptive analytical models, and to complete the research objectives, a questionnaire was prepared consisting of two main axes: the spread of important data. (30) distribution sheets were distributed to employees of the Brega Oil Marketing Company, who were selected within the original study. After analyzing the recovery statement sheets, depending on the famous descriptive analysis, the percentage of percentages and failures were used, and the arithmetic mean was determined. Some of the most important results were the application of international learning to know (IFRS) in a distinguished tool for financial reports, We recommend in the study the development of an international application at the level of quality of financial reports (IFRS).